Some issues of budgetary funding of state servants trainings in the Republic of Armenia - Gyozalyan, Vardush (Bulletin of Yerevan University G: Economics, 2024)
The article examines and systematically analyzes the system of state financing of trainings of civil servants of the Republic of Armenia, using the methods of economic and statistical analysis. The source for the creation of the analysis database were the State budget indicators of different years, including planned, adjusted and actual data. Within the framework of the article, there is studied the best international experience of state support for the organization of trainings (on the example of OECD countries) and the possibilities of its localization in RA. There are analized the dynamics and trends of the share of additional education (mainly includes the trainings) in the state budget, problems and gaps in the system of state funding of trainings are revealed according to directions and departments. Based on the analysis, there were made a number of suggestions to improve the system, which will contribute to the qualitative improvement and efficiency of trainings, and the formation of healthy competition among employees. In particular, it is proposed to review the training participation planning system, based on the study of real demand and the implementation of evidence-based policies, which will allow both to save public funds and to organize training according to effective targets.